Chronic Isolated Fallopian Tube Torsion in a Sexually Inactive Adolescent Female Diagnosed Peroperatively - Yuhya Hirahara; Koichi Nagai; Kazunori Mukaida (Case Reports in Surgery)
Introduction. Isolated fallopian tube torsion (IFTT) has rarely been confirmed in sexually inactive adolescents, and preoperative diagnosis of IFTT is difficult because of the absence of specific symptoms. Therefore, pediatric patients with IFTT tend to be misdiagnosed before the surgery. Case. A 15-year-old female patient with no history of abdominal surgery or sexual intercourse presented with acute left lower abdominal pain and purpura. MRI revealed hydrosalpinx in the left adnexal region. Her abdominal pain had completely resolved at our examination; she was followed up as an outpatient. One month after the initial presentation, she experienced a large volume of watery discharge. Magnetic resonance imaging, which was performed every three months, showed a gradual decrease in the size of the hydrosalpinx; however, it persisted in the left adnexal region. She was counseled to receive laparoscopy to treat the hydrosalpinx, which was the most likely cause of the watery discharge. IFTT was detected during the laparoscopy, and left salpingectomy was performed for pathological evaluation of the persistent hydrosalpinx. Following laparoscopy, the patient’s watery discharge was resolved. Pathological findings confirmed no signs of malignancy. Conclusion. Our current report highlighted watery discharge as an indicative symptom of IFTT. It is unclear whether IFTT induced the hydrosalpinx or vice versa. We presumed that the patient’s hydrosalpinx occurred due to IFTT, because the patient complained watery discharge one month after the initial appearance, and noncongenital hydrosalpinx in adolescents, especially without a history of sexual intercourse, is a rare event. Clinicians should consider IFTT in patients presenting with unremitting watery discharge and hydrosalpinx, because IFTT may persist even after the pain disappears.